2014
DOI: 10.1242/jeb.109363
|View full text |Cite
|
Sign up to set email alerts
|

Sound production inOnuxodon fowleri(Carapidae) and its amplification by the host shell

Abstract: Onuxodon species are well known for living inside pearl oysters. As in other carapids, their anatomy highlights their ability to make sounds but sound production has never been documented in Onuxodon. This paper describes sound production in Onuxodon fowleri as well as the anatomy of the sound production apparatus. Single-pulsed sounds and multiple-pulsed sounds that sometimes last more than 3 s were recorded in the field and in captivity (Makemo Island, French Polynesia). These pulses are characterized by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Staccatos are interesting because the same kind of long-duration sounds were also recorded in O. fowleri (Kéver et al 2014). In this species, sounds could be detected at 40 m from the emitter, which implies that these regular beats are made to attract conspecifics.…”
Section: Galley Proofmentioning
confidence: 71%
See 2 more Smart Citations
“…Staccatos are interesting because the same kind of long-duration sounds were also recorded in O. fowleri (Kéver et al 2014). In this species, sounds could be detected at 40 m from the emitter, which implies that these regular beats are made to attract conspecifics.…”
Section: Galley Proofmentioning
confidence: 71%
“…Parasite species feed on the internal tissues of their host, mainly the gonads (Arnold 1956, Trott 1970, Parmentier and Das 2004, Parmentier and Michel 2013. Another interesting aspect of this group of fishes is their ability to produce sounds (Parmentier et al 2003a,b, 2008, Kéver et al 2014. In captivity, series of pulsed sounds have been recorded for Carapus boraborensis (Kaup, 1856), Carapus homei (Richardson, 1846), and Encheliophis gracilis (Bleeker, 1856), only after an individual had entered a sea cucumber that was already occupied by a conspecific or a heterospecific organism (Parmentier et al 2003b, Lagardère et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high percentage of empty stomachs observed in O. fowleri might be related to the time of sampling (10:00 am -3:00 pm). Recently, Kéver et al (2014) reported that the majority of sounds produced by O. fowleri in the field were recorded between 5:00 PM and 12:00 AM, which implies a nocturnal activity in this species. Assuming that O. fowleri forages for food mainly at night, it is thus likely that most of the stomach contents were empty because they were opened during daytime.…”
Section: Discussionmentioning
confidence: 98%
“…Among this fish family, members of a third genus (Onuxodon) are also known to live inside bivalves, being located between the mantle and the shell (Fowler 1927, Trott 1970, Tyler 1970). Fowler's pearlfish, Onuxodon fowleri (Smith, 1955) (Carapinae: Echiodontini), lives inside representatives of the pearl oyster P. margaritifera (Fowler 1927, Parmentier et al 2000, Kéver et al 2014. Onuxodon fowleri is considered a commensal species that uses its host as a shelter and leaves it to feed on small benthic preys such as annelids and small crustaceans (Trott 1981, Parmentier et al 2000.…”
Section: Introductionmentioning
confidence: 99%